Caracterização da função mastigatória em pacientes com doenças reumáticas - Almeida, Leylane Fonseca (2017)
The term rheumatic diseases has a considerable impact on patients in terms of physical, psychological and social terms. This term may refer to a group of diseases that affects joints, muscles, skeleton and the stomatognathic system, involving in many cases the temporomandibular joint, restriction of mouth opening, alterations in speech, voice, chewing and swallowing. The objective of this study was to characterize the masticatory function in patients with rheumatic diseases, aiming to make future proposals for interdisciplinary action possible. This is a cross-sectional observational study regarding a series of cases carried out in two stages: clinical evaluation of the masticatory function with a study group composed of adult / elderly individuals of both genders, from the Rheumatology Department of the University Hospital of Federal University of Sergipe,and a control group with subjects without orofacial complaints. At the second moment, the subjects answered a questionnaire for self-evaluation of the masticatory function. The results evidenced alterations in the chewing process stages of the patients and showed, in the self-assessment, a negative perception of their mastication. It is hoped that this work contributed to the elucidation of existing gaps in the scientific literature,in order to better understand the characteristics of the stomatognathic system in these diseases, aiming to improve the quality of life of the subjects, as well as greater and better knowledge of the professionals involved with the diagnosis, prognosis and intervention. It has relevance for being a pioneering work regardinginterdisciplinarywork, involving Speech, Language and Hearing Sciencesand Rheumatology.